Factors Affecting the Behavioral Intention of using Sedayuone Mobile Application - Yanfi, Yanfi; Kurniawan, Yohannes; Arifin, Yulyani (ComTech: Computer, Mathematics and Engineering Applications, 2017)
This research evaluated the factors that influenced the behavioral intention to use a mobile application. The case study used was SedayuOne mobile application. The method used was the questionnaires using Unified Theory of Acceptance and Use of Technology (UTAUT2) model. The questionnaires were sent to the 342 members by using email. The result shows that the user habit is the highest factor that influences the user behavioral intention to consume the SEDAYUONE application.Therefore, to maintain the user behavior, the company must know the user habit and consider promotional strategies to enhance the attractiveness and maintain customer loyalty.